DOES CO-BRANDING, SOCIAL MEDIA MARKETING, AND KEY OPINION LEADERS INFLUENCE PURCHASE DECISIONS IN GREATER JAKARTA AREA - Samuel, Sylvia (SEEIJ (Social Economics and Ecology International Journal), 2024)
Kopi Janji Jiwa is currently one of Indonesia's largest-selling coffee shops. Kopi Janji Jiwa will continue increasing sales to influence many people to purchase. The researcher is also interested in researching the Kopi Janji Jiwa, which is in great demand by the Indonesian people. This study aims to find promotional methods that increase purchasing decisions for Kopi Janji Jiwa in DKI Jakarta. The chosen method is co-branding, social media marketing, and key opinion leaders. First, researchers chose co-branding because co-branding is one of the well-known promotional methods of collaboration between brands. Social media marketing is one of the most effective promotional methods in the modern era, using social networks to reach consumers' interest in a particular product. Finally, a key opinion leader is also one of the most effective methods in the modern era. It is a way to attract buyers or consumers to a brand by using someone's popularity to influence their followers to buy the brand or product. The results obtained from processing 354 data samples show that co-branding, social media marketing, and key opinion leaders significantly influence the purchasing decision of the Kopi Janji Jiwa in DKI Jakarta. The technique used in this research is non-probability sampling with the purposive sampling method, using a total sample of 200 data. The research that has been conducted has concluded that co-branding and social media marketing have a significant effect on purchasing decisions. However, key opinion leaders do not affect buying decisions for Kopi Janji Jiwa in DKI Jakarta.